Numerical Study of the Thermal Behavior of a Composite Phase Change Material (PCM) Room - Ben Khedher, N. (Engineering, Technology & Applied Science Research, 2018)
In this study, thermal performance of building walls integrated with phase change materials (PCM) was evaluated in terms of indoor temperature reduction and heat transfer time delay. PCM was incorporated as thin layer placed longitudinally within walls. The thermal performance of a room with and without PCM was evaluated numerically. The developed model is based on the enthalpy formulation for PCM melting and solidification, which is solved by an implicit finite difference method. The effect of PCM type on heat gain indoors was studied. Three phase change materials (n-octadecane, n-eicosane and calcium chloride hexahydrate) were tested in hot weather. Results showed that octadecane is the best in ensuring an indoor temperature close to 27 °C for the test room. Moreover, optimal thickness of the PCM layer within the walls is critical for heat transfer reduction and management and should be carefully chosen.